2020
DOI: 10.1097/ico.0000000000002636
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Descemet Membrane Endothelial Keratoplasty in Pseudophakic Eyes Compared With Triple-DMEK at 1-Year Follow-up

Abstract: Purpose: To compare the survival rate 1 year after Descemet membrane endothelial keratoplasty (DMEK) in pseudophakic eyes versus combined phacoemulsification and DMEK (triple-DMEK). Methods: Retrospective, interventional, consecutive case series. From all DMEKs performed from January 1, 2017, to June 30, 2018, we selected those performed in pseudophakic eyes (pseudophakic DMEK) and those that underwent triple-DMEK. We compared the survival rate 1 year a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 24 publications
0
25
1
Order By: Relevance
“…Seven non-randomized studies ( n = 1,414 eyes) reported the primary graft failure rate, which was similar between DMEK and “triple DMEK” (RD 0.01; 95% CI: −0.02 to 0.05; I 2 = 34%; p = 0.44; Figure 7A ) ( 21 , 34 , 35 , 43 45 , 48 ). There was no data available regarding primary graft failures among non-comparative DMEK and “triple DMEK” studies.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Seven non-randomized studies ( n = 1,414 eyes) reported the primary graft failure rate, which was similar between DMEK and “triple DMEK” (RD 0.01; 95% CI: −0.02 to 0.05; I 2 = 34%; p = 0.44; Figure 7A ) ( 21 , 34 , 35 , 43 45 , 48 ). There was no data available regarding primary graft failures among non-comparative DMEK and “triple DMEK” studies.…”
Section: Resultsmentioning
confidence: 83%
“…Eight comparative studies ( n = 2,799 eyes), which included 1,408 DMEK eyes and 1,391 “triple DMEK” eyes, reported the postoperative re-bubbling rate ( 21 , 22 , 34 , 35 , 39 , 43 , 45 , 48 ), Re-bubbling was reported in 316 (22.4%) DMEK eyes and 381 (27.4%) “triple DMEK” eyes. The meta-analysis demonstrated that there was no statistical difference between DMEK alone and “triple DMEK” in terms of postoperative re-bubbling rate (RD −0.06; 95% CI: −0.13 to 0.00; I 2 = 73%; p = 0.07; Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that with a larger sample size, this value would have become significant. The literature regarding this issue is discordant: some studies found that triple-DMEK associates with higher levels of postoperative graft detachment [ 41 43 ] whereas others did not observe that triple-DMEK associates with worse rebubbling rates [ 28 , 30 , 44 , 45 ]. Again, the reason for these discrepancies is unclear but it may relate to differences between studies in terms of surgical factors.…”
Section: Discussionmentioning
confidence: 99%
“…It was recorded as either mild (involving less than one-third of the peripheral graft area) or signi cant (involving more than one-third of the graft area or any detachment involving the central visual axis). 4,7 Surgical technique All grafts were prepared by the surgeon in the theatre before the surgery on the same day using a manual dissection technique with modi cations to the originally described method by Melles. 9 Following trephination and creation of a triangular mark to identify the correct orientation 10 , they were transferred into a single-use cartridge connected to tubing and syringe (Geuder injector system; German Geuder AG) just before transplantation.…”
Section: Methodsmentioning
confidence: 99%
“…To prevent this, surgeons often do prophylactic peripheral iridotomy either before, using the Nd-YAG laser or surgical iridectomy during the procedure; despite that, air or gas often needs to be released. [6][7][8] We have been routinely performing DMEK without preoperative PI or intraoperative surgical iridectomy using a standardized protocol for many years. This retrospective study aims to analyze whether avoiding laser iridotomy or surgical iridectomy affects the rates of pupillary block, graft detachment, graft failure and endothelial cell loss compared to those documented in the literature.…”
Section: Introductionmentioning
confidence: 99%